Effect of Clay Content on the Mechanical Properties of Hydrate-Bearing Sediments during Hydrate Production via Depressurization - Dongliang Li; Zhe Wang; Deqing Liang; Xiaoping Wu (Energies, 2019)
The effects of sediments with different clay contents on the mechanical properties of hydrate deposits were studied using a high-pressure, low-temperature triaxial apparatus with in-situ synthesis, as well as the mechanical properties of self-developed hydrate sediments. Through multi-stage loading, triaxial compression tests were conducted by adding quartz sand with different clay contents as the sediment skeleton, and the stress−strain relationship of the shearing process and the strength of sediments with different clay contents were determined. Volumetric changes were also observed during shearing. The results show that the strength of hydrate sediments decreases with the increasing clay content of sediments; in the processes of depressurization and shearing, the hydrate samples exhibited obvious shear shrinkage, regardless of the sediment particle size.